THE ROLE OF INTERNAL AUDIT IN IMPROVING TRANSPARENT FINANCIAL MANAGEMENT AT MUHAMMADIYAH 1 WARU ELEMENTARY SCHOOL, SIDOARJO - Biduri, Sarwenda; Hanif, Aisha; Maryanti, Eny; Firnata, Tifani Angga (Journal of Social Comunity Services, 2026)
Objective: This study aims to explore the implementation of internal audits at SD Muhammadiyah 1 Waru Sidoarjo and analyze their impact on the transparency and accountability of financial reporting. Method: A qualitative approach was employed, with data collected through observation, interviews, and documentation. Results: The findings indicate that internal audits significantly contribute to improving the transparency of financial reports. However, challenges such as limitations in documentation and financial management systems remain, requiring further improvements. Novelty: This research provides valuable insights into the role of internal audits in educational institutions, particularly in enhancing financial transparency and accountability, which has been underexplored in the context of Indonesian schools.